Peningkatan Wisata Berkelanjutan Di Masyarakat Pedesaan Melalui Penyaluran Buku Saku Daily English For Tourism - Alvian, Ali; Khoyali, Alpan; Rustiana, Dila; Maulana, Erik Subandi; Hilpiana, Lina; Hasanah, Maulia; Subakti, Muhammad; Febriani, Neni; Hartanti, Nurul Fitria; Ulfatunnis; Respa Dewi, Wiwin; Mawarzani, Sapka (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2024)
Mastery of English in the tourism industry is one of the important skills that supports the development of the economic sector, especially in tourist villages. In order to support improving English language skills for local communities, we have compiled the book